MANAJEMEN STRATEGIK DALAM PERBANKAN SYARIAH - Sri Anugerah Natalina; Arif Zunaidi (WADIAH, 2021)
The current economic development has led to competition betweencompanies in controlling and maintaining the market. Companies withother companies are competing to be winners in business competition.Likewise, bank or non-bank financial institutions. With the increasingquantity of customers and the growth of the nation's economy, it has madeIslamic banking compete with other Islamic banks to be at the forefront ofproviding satisfaction and controlling customers. A special management isneeded to determine the right strategy in every policy step taken. For thisreason, strategic management is needed so that every policy taken is notmisplaced. Because every mistake in policy making will certainly have anegative impact on the company, either in the form of loss of customers orloss of coffers of income. This writing uses the literary method, whichcollects data based on written texts from various sources to analyze. Theresults can be seen, to win market competition requires strategicmanagement, making a SWOT analysis to determine the strengths andweaknesses of the company. Make an analysis of challenges andopportunities, in order to dominate the market.